Understanding and Expressing The Factors Causing Difficulties of Children In Learning, Especially In The Field Of Reading - Seftiani, Wita; Zakariyah; Aulia, Indo Dini (Yayasan Nurul Yakin Bunga Tanjung, 2023)
The discussion that we present aims to discuss the factors that cause learning difficulties, especially in the field of reading in SD 122/X Sungai Beras students, Mendahara Ulu District, East Tanjung Jabung Regency. From a combination of grades IV, V, and VI, there are 100 students. Of these, there were 7 students who experienced learning difficulties, especially in the field of reading. The data was obtained through interviews with teachers and direct tests on students who claimed to have difficulty reading. This difficulty is caused by factors (internal), namely the talents and interests of students in certain learning situations that are still lacking and there is no compulsion to learn in students which is called lazy, As well as (external) factors, namely the family is a supporter of the learning situation of students but is still lacking, such as; direction from parents who are still lacking, as well as parents who are preoccupied with work which reduces parental attention to their children. Some people think that one of the factors causing difficulties is a condition or situation that creates obstacles in the learning process of students. The discussion used is descriptive method which includes internal and external factors. This means that the reader has a picture of difficulties in learning. Some people think that one of the factors causing difficulties is a condition or situation that creates obstacles in the learning process of students. The discussion used is descriptive method which includes internal and external factors. This means that the reader has a picture of difficulties in learning. Some people think that one of the factors causing difficulties is a condition or situation that creates obstacles in the learning process of students. The discussion used is descriptive method which includes internal and external factors. This means that the reader has a picture of difficulties in learning.